Pelatihan Pemanfaatan Teknologi Dalam Observasi Lapangan Oleh Mahasiswa Universitas Muhammadiyah Makassar dengan Mahasiswa Universitas Lakidende - Syamsuri, Andi Makbul; Rumata, Nini Apriani; Nurhidayat, M.; Haerul, Muh. Farhan (Jurnal BALIRESO, 2023)
In a plan requires an accurate analysis. Accurate analysis results are determined by the accuracy of the data obtained during field observations. At this time the development of technology is developing very rapidly. This is in line with the technology that can be used when conducting field observations in an area. The problem that often arises is the procurement of field observations in data collection is still done manually so that the results of these observations tend to be inaccurate and take a very long time to complete. The purpose of this service is to increase knowledge in the use of technology for field observations or surveys between the Regional and City Planning Study Program at Muhammadiyah Makassar University and the Urban and Regional Planning Study Program at Lakidende University. The method of this service is training in the use of appsheet applications and the use of drones to take satellite images of areas that already have coordinates. The results of the use of these two technologies are then expected to provide benefits in field observations, especially identifying areas and the availability of facilities and infrastructure accurately. The implementation is in the form of assistance for training, practical assistance and evaluation of the success of activities.